Effects of salt substitute on home blood pressure differs according to age and degree of blood pressure in hypertensive patients and their families - Hu, Jihong; Zhao, Liancheng; Thompson, Brian; Zhang, Yawei; Wu, Yangfeng (Clinical and experimental hypertension (1993), 2018)
Background: It is known that home blood pressure (HBP) is a more reliable assessment of hypertension treatments than clinical blood pressure (BP). Despite this, HBP response to a salt substitute has only been evaluated by one study which, did not look at the salt substitute's effect on family members and did not analyze by age, gender, or BP degree. The aim of this current study was to assess the effects of a low-sodium and high-potassium salt substitute on HBP among hypertensive patients and their family members. Methods: A total of 220 households (including 220 hypertensive patients and 380 their families) were randomly assigned to the regular salt or salt substitute groups. HBP was measured at the beginning, 3rd, 6th, and 12th months. Among the patients (n = 220), only home systolic blood pressure (HSBP) was significantly reduced, by an adjusted baseline BP of 4.2 mm Hg (95% CI: 1.3-7.0 mm Hg), in the salt substitute group compared with those in the regular salt group at each visit (all P < 0.05). There were no detectable differences between groups for home diastolic blood pressure (HDBP) at any visit. Among the family members, HSBP and HDBP were not significantly different between the groups. Furthermore, Individuals ≥60 years old, hypertensive patients with stage-2 hypertension, family members with hypertension, and women experienced greater HSBP reduction. Conclusions: Older subjects, those with higher blood pressure, and women experienced greater home blood pressure reduction from the salt substitute compared to regular salt.